Notes on two subantarctic pannariaceous lichens - Jørgensen, Per Magnus (Cryptogamie Mycologie, 2005)
It is shown by use of a newly discovered, old photo of the missing type that Siphulina orphnina (Hue) C. W. Dodge is identical with Pannaria caespitosa P. M. Jorg. The new combination Pannaria orphnina (Hue) R M. Jorg. is made, and the name neotypitied. Parmeliella austroshetlandica Sochting & Ovstedal is shown to be a species in the small subantarctic genus Peltularia R. Sant. (Coccocarpiaceae), and is transferred to that genus.
Keywords: Antarktis; biologi; botanikk; lav; planter

Additions and corrections to the Lichens of Antarctica and South Georgia - Øvstedal, Dag; Smith, Ronald I. Lewis (Cryptogamie, Mycologie, 2004)
The taxonomic listing given in Lichens of Antarctica and South Georgia (Øvstedal & Lewis Smith 2001) has been updated. 17 additional taxa of lichenised fungi are described, including several nomenclatural changes. 14 of these are considered as new records for the Antarctic and one is new to South Georgia. One is described as new to science.
https://sciencepress.mnhn.fr/sites/default/files/articles/pdf/cryptogamie-mycologie2004v25f4a2.pdf
Keywords: Antarktis; biogeografi; botanikk; lav; planter; taksonomi

Seaweeds in Cold Seas: Evolution and Carbon Acquisition - Raven, John A.; Johnston, Andrew M.; Kübler, Janet E.; Korb, Rebecca; Mcinroy, Shona G.; Handley, Linda L.; Scrimgeour, Charlie M.; Walker, Diana I.; Beardall, John; Clayton, Margaret M.; Vanderklift, Mathew; Fredriksen, Stein; et al. (Annals of Botany, 2002)
Much evidence suggests that life originated in hydrothermal habitats, and for much of the time since the origin of cyanobacteria (at least 2·5 Ga ago) and of eukaryotic algae (at least 2·1 Ga ago) the average sea surface and land surface temperatures were higher than they are today. However, there have been at least four significant glacial episodes prior to the Pleistocene glaciations. Two of these (approx. 2·1 and 0·7 Ga ago) may have involved a ‘Snowball Earth’ with a very great impact on the algae (sensu lato) of the time (cyanobacteria, Chlorophyta and Rhodophyta) and especially those that were adapted to warm habitats. By contrast, it is possible that heterokont, dinophyte and haptophyte phototrophs only evolved after the Carboniferous–Permian ice age (approx. 250 Ma ago) and so did not encounter low (≤5 °C) sea surface temperatures until the Antarctic cooled some 15 Ma ago. Despite this, many of the dominant macroalgae in cooler seas today are (heterokont) brown algae, and many laminarians cannot reproduce at temperatures above 18–25 °C. By contrast to plants in the aerial environment, photosynthetic structures in water are at essentially the same temperature as the fluid medium. The impact of low temperatures on photosynthesis by marine macrophytes is predicted to favour diffusive CO2 entry rather than a CO2‐concentrating mechanism. Some evidence favours this suggestion, but more data are needed.
Keywords: Sørishavet; alger; biogeografi; botanikk; makroalger; marin biologi